2016
DOI: 10.1108/ijem-12-2014-0162
|View full text |Cite
|
Sign up to set email alerts
|

Primary school principals ' job satisfaction and occupational stress

Abstract: Purpose – The purpose of this paper is to explore the factors associated with occupational stress and job satisfaction among Irish primary school principals. A principal’s job has become increasingly demanding and complex in recent decades. However, there is little current research into their levels of stress and job satisfaction, particularly based on nationally representative data. In order to understand how principals perceive their job and how best to support them, new insights into factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
158
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(182 citation statements)
references
References 27 publications
9
158
3
2
Order By: Relevance
“…Queen & P. S. Queen, 2005). It, therefore, appears that principals are under more pressure (Boyland, 2011) due to several changes in recent years that have increased the variety, scope, and demands of the position resulting in many principals considering leaving the profession (Mitchell, 2010) or unwilling to accept position as principals (Darmody & Smyth, 2016).…”
Section: School Principal and Sources Of Job Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Queen & P. S. Queen, 2005). It, therefore, appears that principals are under more pressure (Boyland, 2011) due to several changes in recent years that have increased the variety, scope, and demands of the position resulting in many principals considering leaving the profession (Mitchell, 2010) or unwilling to accept position as principals (Darmody & Smyth, 2016).…”
Section: School Principal and Sources Of Job Stressmentioning
confidence: 99%
“…Consequently, if the needs of the work are more than what the individual's ability can contain, then job stress is likely to result. The resultant job stress which is demonstrated visibly in the form of unpleasant negative emotions (anger, anxiety, tension, frustration, or depression) (Kyriacou, 2001), have impact on the individual's work performance (Darmody & Smyth, 2016;Mbibi, Oluchi, & Nwamuo, 2013). In the long term, the inability of the individual's capacity (competency or skills) to match the demand of the job give rise to job burnout, and according to Brock and Grady (2002), the symptoms of burnout are shown as physical, intellectual, social, emotional, and spiritual.…”
Section: School Principals and Effect Of Job Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The second emerging question focuses on the potential effect that democratic school leadership could have on relieving educational administrators of their managerial obligations. Research has shown that principals in Canada are experiencing an increase in work intensification (Pollock, Wang, & Hauseman, 2014, 2017 which has led to more physical and emotional stress (Chaplain, 2001;Darmody & Smyth, 2016). As can be seen in Mervin's case, distributing his managerial obligations to others resulted in a perceived increase in time afforded to lead.…”
Section: Resultsmentioning
confidence: 99%